Association between Age of Menopause and Thickness of Crestal Cortical Bone at Dental Implant Site: A Cross-Sectional Observational Study - Dinesh Kumar; Sahba Hassan; Madhu S. Ratre; Shailesh Jain; Rajesh K. Gupta; Nikhil P. Agnihotri (Journal of Pharmacy and Bioallied Sciences, 2025)
Objective: Menopause, the natural biological transition marking the end of a woman’s reproductive years. The study’s main objective is to find an association between menopause age and the thickness of crystal cortical bone at the dental implant site. Methodology: Data were collected from 155 postmenopausal women who have undergone dental implant placement. Results: In the early menopause group (≤45 years), the average bone thickness was 4.2 ± 1.0 mm at the mesial, 3.8 ± 0.9 mm at the mid, and 4.1 ± 1.2 mm at the distal site, with an overall average of 4.0 ± 1.1 mm. In contrast, the late menopause group (>45 years) had an average bone thickness of 3.3 ± 1.1 mm at the mesial, 3.1 ± 1.0 mm at the mid, and 3.2 ± 1.1 mm at the distal site, with an overall average of 3.2 ± 1.0 mm. Conclusion: It is concluded that the age of menopause plays a significant role in determining the thickness of the crestal cortical bone at dental implant sites in postmenopausal women.